A simple general process model for vibratory finishing. Issue 9 (October 2016) - Wan, Stephen; Liu, Yu; Woon, Keng
Abstract The present work re-derives a general process model for loose abrasive processes, starting from the interpretation that, during the phase of constant stock removal (equilibrium phase), the surface roughness is actually in dynamic equilibrium about an equilibrium surface roughness, instead of the previous assumption that it tends monotonically to a limiting value. The new model better accounts for the surface roughness evolution seen in both two very different types of vibratory finishing process experiments: very aggressive roughening experimental runs versus more "subtle", controlled ones. In fact, the original model is a special case, in which the dynamics in the equilibrium phase is highly attenuated and hence still applicable to well-controlled loose abrasive processes such as abrasive flow machining and magnetorheological finishing.